VD_FINDINFO Jug / 2014 / 166 vom 12. Juni 2014 - VD Tribunal cantonal (2014)
PRÉVOYANCE PROFESSIONNELLE, DIVORCE, PARTAGESENS GÉNÉRAL, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 al. 1 CC, 22 al. 1 LFLP, 7 OLP, 8a al. 1 OLP, 12 OPP2, 93 al. 1 let. a LPA-VD